Empirical issues in lifetime poverty measurement - Michael Hoy; Brennan Scott Thompson; Buhong Zheng (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper demonstrates the implications of adopting an approach to measuring poverty that takes into account the lifetime experience of individuals rather than simply taking a static or cross-sectional perspective. Our approach follows the theoretical innovations in Hoy and Zheng (2008) which address various aspects of the specific pattern of any poverty spells experienced by an individual as well as a possible retrospective consideration that an individual might have concerning his life experience as a whole. For an individual, our perspective of lifetime poverty is influenced by both the snapshot poverty of each period and the poverty level of the permanent lifetime consumption; it is also influenced by how poverty spells are distributed over the lifetime. Using PSID data for the US, we demonstrate empirically the power of alternative axioms concerning how lifetime poverty should be measured when making pairwise comparisons of individual lifetime profiles of consumption (income) experiences. We also demonstrate the importance of taking a lifetime view of poverty in comparing poverty between groups by use of the classic FGT 'snapshot' poverty index in conjunction with period weighting functions that explicitly reflect concerns about the pattern of poverty spells over individuals' lifetimes.
Keywords: I32; 330; Lifetime poverty; snapshot poverty; chronic poverty; early poverty; poverty measurement